2020
DOI: 10.3390/cancers13010018
|View full text |Cite
|
Sign up to set email alerts
|

A Paradigm Revolution or Just Better Resolution—Will Newly Emerging Superresolution Techniques Identify Chromatin Architecture as a Key Factor in Radiation-Induced DNA Damage and Repair Regulation?

Abstract: DNA double-strand breaks (DSBs) have been recognized as the most serious lesions in irradiated cells. While several biochemical pathways capable of repairing these lesions have been identified, the mechanisms by which cells select a specific pathway for activation at a given DSB site remain poorly understood. Our knowledge of DSB induction and repair has increased dramatically since the discovery of ionizing radiation-induced foci (IRIFs), initiating the possibility of spatiotemporally monitoring the assembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 198 publications
(345 reference statements)
1
46
0
Order By: Relevance
“…We showed that inhibiting OGT leads to more condensed chromatin, whilst inhibition of OGA induces a global chromatin relaxation. As it was found that, upon DNA damage, chromatin decompaction is stimulated globally [ 28 , 49 ], but also locally [ 27 , 50 , 51 ], and since it is known that within repair of DNA damage the chromatin status is crucial for the repair-pathway choice and the recruitment of DSB repair factors [ 26 , 52 ], we conclude that O-GlcNAcylation may also impact on the DSBs response by regulating chromatin remodeling. This is supported by several findings that OGT and OGA modulate recruitment, stability and activity of key chromatin regulators [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We showed that inhibiting OGT leads to more condensed chromatin, whilst inhibition of OGA induces a global chromatin relaxation. As it was found that, upon DNA damage, chromatin decompaction is stimulated globally [ 28 , 49 ], but also locally [ 27 , 50 , 51 ], and since it is known that within repair of DNA damage the chromatin status is crucial for the repair-pathway choice and the recruitment of DSB repair factors [ 26 , 52 ], we conclude that O-GlcNAcylation may also impact on the DSBs response by regulating chromatin remodeling. This is supported by several findings that OGT and OGA modulate recruitment, stability and activity of key chromatin regulators [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 74%
“…The role of O-GlcNAc on chromatin architecture in the context of the DDR has not been studied yet. However, since the chromatin status is crucial for DSB-repair processes [ 26 ], O-GlcNAcylation might impact on DSB repair that way as well. To this end, we made use of a recently established method based on FLIM [ 27 , 28 ] to identify effects of O-GlcNAcylation on the chromatin compaction status after treating the cells with OGT or OGA inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Among all kinds of ionizing radiation induced biological effects, damages to chromatin especially the DNA molecules in the nucleus of cells are thought to be the most severe with respect to cellular survival and carcinogenesis [2,5,32,33]. DNA base oxidation, single strand breaks (SSBs) and double strand breaks (DSBs) are the most common ionizing radiation induced damages to the DNA molecule, that affect genome integrity and DNA biochemistry [34].…”
Section: Damages Of Dna Induced By Ionizing Radiationmentioning
confidence: 99%
“…and biological (e.g., developmental and proliferative state of the affected cell type) factors. As the overall organismal radiation response results from the entirety of all individual radiation responses on the single cell level, deeper understanding of the underlying, complex molecular mechanisms and dynamics of radiation induced DNA damaging and repair on the cellular level is highly relevant for fundamental and applied radiation biology (for review see [1,2,5]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation